High temperature Ni45Co5Mn25 − xFexGa20Cu5 ferromagnetic shape memory alloys. (June 2017) - Pérez-Checa, A.; Feuchtwanger, J.; Musiienko, D.; Sozinov, A.; Barandiaran, J.M.; Ullakko, K.; Chernenko, V.A.
Abstract: We anticipated that replacing Mn by Fe in the Ni50 − y Coy Mn25 − x Fex Ga25 − z Cuz magnetic shape memory alloys would increase their Curie temperature and spontaneous magnetization. In particular, in the set of alloys Ni45 Co5 Mn25 − x Fex Ga20 Cu5 (x = 0, …8), a record-breaking combination of high martensitic transformation temperature (400 K) and Curie temperature (458  K ) has been achieved for Ni45 Co5 Mn21 Fe4 Ga20 Cu5 . This alloy shows a non-modulated tetragonal martensite with the lowest lattice distortion ratio, c/a = 1.15, near the reverse martensitic transformation temperature. Because of the high Curie temperature and low c/a ratio, the Ni45 Co5 Mn25 − x Fex Ga20 Cu5 and Ni50 − y Coy Mn25 − x Fex Ga25 − z Cuz alloys are promising candidates for high temperature magnetic shape memory applications. Graphical abstract: